Light emitting diode based on cubic phase perovskite thin film and preparation method thereof

By introducing the self-polymerized additive N-vinylpyrrolidone (NVP) into the perovskite light emitting diode, a high-quality, low-defect cubic phase perovskite film was prepared, which solved the problem of high ion migration and achieved a high brightness and stable green light emitting diode.

CN119894329AActive Publication Date: 2025-04-25HENAN FLEXIBLE ELECTRONICS IND TECH RES INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411740405.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-25
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The perovskite light-emitting diodes have high ion migration problems during the preparation process, resulting in lattice collapse and emission wavelength spectral displacement. The existing capping ligands are insufficient, making it difficult to suppress ion migration for a long time.

Method used

A three-dimensional perovskite film was prepared by a one-step solution deposition method. By introducing the self-polymerized additive N-vinylpyrrolidone (NVP), it uses its strong hydrogen bond and coordination bond to perovskite to passivate the crystal surface defects and induce the formation of high-quality and low-defect cubic phase grains.

Benefits of technology

The preparation of high-brightness and stable green light perovskite light emitting diodes is achieved, which improves the brightness and electrical-light conversion efficiency of the device, enhances the stability of the film, and extends the carrier life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894329A_ABST
    Figure CN119894329A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of light-emitting materials and devices, and particularly relates to a light-emitting diode based on a cubic-phase perovskite thin film and a preparation method of the light-emitting diode. The method comprises the following steps: S1, preparing a precursor solution: dissolving FABr, MABr, GABr, CsBr and PbBr2 in DMSO (dimethylsulfoxide) to obtain a mixed cationic precursor solution, and then adding N-vinyl pyrrolidone and azodiisobutyronitrile to obtain the precursor solution; s2, cleaning and drying the conductive substrate; s3, the conductive substrate is coated with a mixed solution of PEDOT: PSS and PFI, annealing is carried out, and a hole transport layer is obtained; s4, coating the hole transport layer with the precursor solution, then dropwise adding an anti-solvent, and obtaining a cubic-phase perovskite thin film after annealing; and S5, depositing an electron transport layer and a cathode on the perovskite thin film. The perovskite thin film prepared by the invention has a low-defect cubic phase structure, and the brightness and the electro-optical conversion efficiency of a device can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of light-emitting materials and devices, and in particular relates to a light-emitting diode based on a cubic phase perovskite film and a preparation method thereof. Background Art

[0002] Metal halide perovskites have become attractive semiconductor materials in the past decade due to their excellent optoelectronic properties and are widely used in a variety of devices such as solar cells and photodetectors. As direct bandgap materials, they have easily adjustable band gaps, high carrier mobility, and excellent color purity, which make them emerging semiconductors in the field of light-emitting diode applications. Bromine-based perovskites have been successfully used in perovskite light-emitting diodes, achieving an external quantum efficiency of more than 30%.

[0003] In order to achieve the ideal performance of perovskite light-emitting diodes, the structure of perovskite nanocrystals can be finely controlled to effectively confine carriers, thereby increasing the exciton binding energy, increasing the probability of radiative recombination, and improving the photoluminescence quantum yield. However, due to the uneven nucleation process of perovskites and the rapid crystallization rate, the reduction of grain size is often accompanied by the appearance of a large number of grain boundaries and high surface trap density, which will lead to an increase in non-radiative recombination and a decrease in device performance. Therefore, when preparing high-performance perovskite light-emitting diodes, controlling the growth of films and passivating surface traps are essential steps. In addition, controlling the crystal orientation in polycrystalline films can also enhance the charge transport efficiency by reducing structural disorder. Various strategies have been reported for regulating the crystallization process and passivating the perovskite surface, including the use of organic or inorganic additives, optimizing deposition techniques, and solvent engineering. These strategies can act as capping ligands. However, the high ion activity and biased ion migration in perovskite films are another bottleneck problem that needs to be solved. Severe ion migration will produce a large number of ion vacancies, which will lead to the collapse of the lattice. In addition, ion migration is also one of the reasons for the spectral shift of the emission wavelength of perovskite light-emitting diodes, especially in mixed anion and mixed cation perovskite light-emitting diodes.

[0004] To prevent this from happening, capping ligands can be used to confine ions in small crystals. However, most of these ligands are dynamic and have few anchoring sites on the perovskite, making it difficult to ensure long-term stability, which may eventually lead to an increase in bias. In contrast, polymer-based additives with abundant anchoring sites have been shown to effectively encapsulate perovskite solar cells and regulate directional crystallization and surface morphology, thereby suppressing ion migration and improving device stability. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a light-emitting diode based on a cubic phase perovskite film. The present invention is based on a one-step solution deposition method to prepare a three-dimensional perovskite film, which is simple to operate and provides technical support for the preparation of a new type of high-brightness, stable green light perovskite light-emitting diode.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a light-emitting diode based on a cubic perovskite film comprises the following steps:

[0008] S1. Prepare a precursor solution: dissolve FABr, MABr, GABr, CsBr and PbBr2 in DMSO to obtain a mixed cationic precursor solution, and then add N-vinyl pyrrolidone and azobisisobutyronitrile to obtain a precursor solution;

[0009] S2, cleaning and drying the conductive substrate;

[0010] S3, coating a mixed solution of PEDOT:PSS and PFI on a conductive substrate, and annealing to obtain a hole transport layer;

[0011] S4, coating the precursor solution on the hole transport layer, then dropping an anti-solvent, and obtaining a cubic perovskite film after annealing;

[0012] S5. Depositing an electron transport layer and a cathode on the perovskite film.

[0013] The reaction structure of polyvinyl pyrrolidone (PVP) obtained by the reaction of N-vinyl pyrrolidone (NVP) is shown below:

[0014]

[0015] The present invention does not specifically limit the material of the electron transport layer, and those skilled in the art can select materials with similar properties to TPBi and TmPyPb. The present invention does not specifically limit the material of the cathode, and those skilled in the art can select commonly used cathode materials such as metal aluminum, silver, and gold.

[0016] Furthermore, the molar ratio of FABr, MABr, GABr, CsBr and PbBr2 in step S1 is (0.74-0.76):(0.1-0.2):(0.2-0.25):(0.1-0.13):1.

[0017] Furthermore, the usage ratio of PbBr2 to DMSO in step S1 is 1 mol:(1-2) mL.

[0018] Furthermore, the amount of N-vinyl pyrrolidone used in step S1 is 2.5-20% of the volume of DMSO.

[0019] Furthermore, the amount of azobisisobutyronitrile used in step S1 is 0.1-0.5% of the mass of N-vinyl pyrrolidone.

[0020] Furthermore, the anti-solvent in step S4 is a chlorobenzene solution of 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene, wherein the concentration of 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene in chlorobenzene is 0.5-2 mg / mL.

[0021] Furthermore, the annealing temperature in step S3 is 140-150° C. and the time is 30-45 min.

[0022] Furthermore, the annealing temperature in step S4 is 75-85° C. and the time is 8-15 min.

[0023] The second object of the present invention is to provide a light-emitting diode based on a cubic phase perovskite film. The perovskite film prepared by the present invention has a high-quality, low-defect cubic phase structure, which realizes the preparation of high-brightness, stable green light perovskite light-emitting diodes, and can effectively improve the brightness of the device and improve the electrical-to-optical conversion efficiency of the device.

[0024] A light emitting diode based on a cubic perovskite film is prepared by using the above preparation method.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention uses a cross-linking strategy and selects N-vinyl pyrrolidone (NVP) self-polymerizing additive to dope the three-dimensional green light perovskite film, and prepares a film with high-quality, low-defect cubic phase grains, and finally realizes a high-brightness, stable green light perovskite light-emitting diode. During the spin coating process, NVP repels the impurities around the grains, allowing the perovskite to nucleate rapidly and delay crystallization; during the annealing process, NVP undergoes a polymerization reaction to form polyvinyl pyrrolidone, which wraps the grains. The C=O double bond in NVP forms a strong hydrogen bond with the A-site cation and with the uncoordinated Pb 2+ Form coordination bonds, passivate crystal surface defects, and induce the formation of cubic phase grains.

[0027] 2. The present invention characterizes the electrical properties of the device and finds that after NVP is introduced into the perovskite light-emitting layer, the current density decreases with the increase of NVP doping concentration. This is because the incorporation of NVP affects the injection and transmission of carriers; with the increase of NVP doping concentration, the brightness of the device first increases and then decreases. This is because a small amount of NVP can passivate defects well, inhibit non-radiative recombination, improve device performance, and improve device stability. However, when more NVP is incorporated, the defect tolerance of NVP is low, resulting in a significant decrease in performance. After comprehensive analysis, the optimal NVP doping amount is 5 Vol.%.

[0028] 3. The self-polymerizing molecule NVP of the present invention increases the exciton binding energy of the perovskite film, which is conducive to the radiative recombination of the excitons, thereby effectively extending the carrier lifetime; an energy level structure that better matches the energy level of the transport layer is obtained, which is conducive to the injection and transmission of carriers. In addition, the introduction of NVP molecules enhances the hydrophobicity of the film, thereby improving the stability of the perovskite film and the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The figure is a flow chart of the preparation of the perovskite light-emitting diode of the present invention;

[0030] Figure 2 It is a schematic structural diagram of the perovskite light-emitting diode of the present invention;

[0031] Figure 3 The SEM images of the perovskite thin film surfaces of Examples 1 to 5 of the present invention and Comparative Example 1;

[0032] Figure 4 The SEM cross-sectional images of the perovskite film of Example 1 of the present invention and Comparative Example 1;

[0033] Figure 5 (a) Figure 5 (c) is a TEM image of the perovskite film of Comparative Example 1; Figure 5 (b) Figure 5 (d) is a TEM image of the perovskite film of Example 1;

[0034] Figure 6 (a) to Figure 6 (c) The current density-voltage characteristic curve, brightness-voltage characteristic curve, EQE-current density characteristic curve of the PeLEDs devices of Examples 1 to 5 and Comparative Example 1, respectively. Figure 6 (d) EL spectra of the PeLED prepared in Example 1 at different voltages;

[0035] Figure 7 (a) Figure 7 (b) Trap state density diagrams of the perovskite thin films of Comparative Example 1 and Example 1 of the present invention, respectively;

[0036] Figure 8 (a) Figure 8 (b) PL spectra of the perovskite films prepared in Comparative Example 1 and Example 1, respectively;

[0037] Fig. 9 (a) Fig. 9 (b) PL and EL spectra of the films of Comparative Example 1 and Example 1, respectively;

[0038] Fig.10 This is a graph showing the stability test results of the PeLEDs device at a voltage of 3.4V according to the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further explained below in conjunction with specific embodiments, comparative examples, test examples and drawings.

[0040] In the following examples, comparative examples and test examples, the raw materials and preparation methods used are conventional materials and techniques in the art unless otherwise specified.

[0041] Example 1

[0042] A method for preparing a light-emitting diode based on a cubic perovskite thin film, specifically comprising the following preparation method, the flow chart of the preparation method is as follows Figure 1 As shown:

[0043] S1. The perovskite precursor solution was prepared according to the following formula: FABr, MABr (methyl ammonium bromide), GABr (guanidinium hydrobromide), CsBr and PbBr2 were dissolved in 1 mL of DMSO at a molar ratio of 0.756:0.108:0.216:0.12:1 to prepare a mixed cationic precursor solution (FA 0.7 MA 0.1 GA 0.2 ) 0.9 Cs 0.1 PbBr3, and then add N-vinyl pyrrolidone (NVP) solution equivalent to 5% of the volume of DMSO to the solution (0.3wt% azobisisobutyronitrile equivalent to the mass of N-vinyl pyrrolidone is added to NVP in advance) to obtain a perovskite precursor solution.

[0044] S2: The ITO substrate is ultrasonically cleaned in deionized water, anhydrous ethanol, acetone, and isopropanol in sequence, with each ultrasonic cleaning time being 25 minutes. After the ultrasonic cleaning is completed, the anode substrate is placed in ozone drying for more than 15 minutes until it is completely dry.

[0045] S3: A mixed solution of PEDOT:PSS (Clevios PVP Al4083) and perfluorinated ion (PFI) (PEDOT:PSS / PFI=9:13 v / v) was spin-coated on an O2-treated ITO substrate and then annealed on a hot stage at 150°C for 30 min to obtain a hole transport layer. After baking, it was transferred to a glove box filled with nitrogen.

[0046] S4: TPBi (1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene) was dissolved in chlorobenzene (CB) to prepare an antisolvent (concentration of 1 mg / mL). The solution was stirred at room temperature overnight in a N2 glove box before use.

[0047] The above perovskite precursor solution was spin-coated on the PEDOT:PSS coated substrate at 6000 rpm for 45 s. After a delay of 20 s, 150 μL of TPBi@CB antisolvent was dropped, and the resulting sample was annealed at 80 °C for 10 min to form a perovskite (PNC) film.

[0048] S5: Finally, the thermal evaporation system is used to -4 Under high vacuum conditions of Pa, a ZADN electron transport layer (ETL) (45nm) and LiF / Al electrodes (1nm / 100nm) were deposited on the perovskite film to obtain a perovskite light-emitting diode.

[0049] This embodiment also provides a perovskite light-emitting diode prepared by the above preparation method, the structure of which is as follows Figure 2 shown.

[0050] Example 2

[0051] A method for preparing a light-emitting diode based on a cubic perovskite film, specifically comprising the following preparation method:

[0052] S1. The perovskite precursor solution was prepared according to the following formula: FABr, MABr (methyl ammonium bromide), GABr (guanidinium hydrobromide), CsBr and PbBr2 were dissolved in 1 mL of DMSO at a molar ratio of 0.74:0.1:0.2:0.1:1 to prepare a mixed cationic precursor solution (FA 0.7 MA 0.1 GA 0.2 ) 0.9 Cs 0.1 PbBr3, and then add N-vinyl pyrrolidone (NVP) solution equivalent to 2.5% of the volume of DMSO to the solution (0.1wt% azobisisobutyronitrile equivalent to the mass of N-vinyl pyrrolidone is added to NVP in advance) to obtain a perovskite precursor solution.

[0053] S2 and S3 are the same as in Example 1;

[0054] S4: Dissolve TPBi (1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene) in chlorobenzene (CB) to prepare an antisolvent (concentration of 0.5 mg / mL). Stir the solution at room temperature overnight in a N2 glove box before use. Other steps are the same as in Example 1.

[0055] S5: Finally, the thermal evaporation system is used to -4 Under high vacuum conditions of Pa, a ZADN electron transport layer (ETL) (45nm) and LiF / Al electrodes (1nm / 100nm) were deposited on the perovskite film to obtain a perovskite light-emitting diode.

[0056] This embodiment also provides a perovskite light-emitting diode prepared by the above preparation method.

[0057] Example 3

[0058] A method for preparing a light-emitting diode based on a cubic perovskite film, specifically comprising the following preparation method:

[0059] S1. The perovskite precursor solution was prepared according to the following formula: FABr, MABr (methyl ammonium bromide), GABr (guanidinium hydrobromide), CsBr and PbBr2 were dissolved in 1 mL of DMSO at a molar ratio of 0.76:0.2:0.25:0.13:1 to prepare a mixed cationic precursor solution (FA 0.7 MA 0.1 GA 0.2 ) 0.9 Cs 0.1 PbBr3, and then add N-vinyl pyrrolidone (NVP) solution equivalent to 10% of the volume of DMSO to the solution (0.5wt% azobisisobutyronitrile equivalent to the mass of N-vinyl pyrrolidone is added to NVP in advance) to obtain a perovskite precursor solution.

[0060] S2 and S3 are the same as in Example 1;

[0061] S4: Dissolve TPBi (1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene) in chlorobenzene (CB) to prepare an antisolvent (concentration of 2 mg / mL). Stir the solution at room temperature overnight in a N2 glove box before use. Other steps are the same as in Example 1.

[0062] S5: Finally, the thermal evaporation system is used to -4 Under high vacuum conditions of Pa, a ZADN electron transport layer (ETL) (45nm) and LiF / Al electrodes (1nm / 100nm) were deposited on the perovskite film to obtain a perovskite light-emitting diode.

[0063] This embodiment also provides a perovskite light-emitting diode prepared by the above preparation method.

[0064] Example 4

[0065] A method for preparing a light-emitting diode based on a cubic perovskite film, specifically comprising the following preparation method:

[0066] S1. The perovskite precursor solution was prepared according to the following formula: FABr, MABr (methyl ammonium bromide), GABr (guanidinium hydrobromide), CsBr and PbBr2 were dissolved in 1 mL of DMSO at a molar ratio of 0.75:0.11:0.22:0.12:1 to prepare a mixed cationic precursor solution (FA 0.7 MA 0.1 GA 0.2 ) 0.9 Cs 0.1 PbBr3, and then add N-vinyl pyrrolidone (NVP) solution equivalent to 15% of the volume of DMSO to the solution (0.4wt% azobisisobutyronitrile equivalent to the mass of N-vinyl pyrrolidone is added to NVP in advance) to obtain a perovskite precursor solution.

[0067] S2 and S3 are the same as in Example 1;

[0068] S4: Dissolve TPBi (1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene) in chlorobenzene (CB) to prepare an antisolvent (concentration of 1 mg / mL). Stir the solution at room temperature overnight in a N2 glove box before use. Other steps are the same as in Example 1.

[0069] S5: Finally, the thermal evaporation system is used to -4 Under high vacuum conditions of Pa, a ZADN electron transport layer (ETL) (45nm) and LiF / Al electrodes (1nm / 100nm) were deposited on the perovskite film to obtain a perovskite light-emitting diode.

[0070] This embodiment also provides a perovskite light-emitting diode prepared by the above preparation method.

[0071] Example 5

[0072] A method for preparing a light-emitting diode based on a cubic perovskite film, specifically comprising the following preparation method:

[0073] S1. The perovskite precursor solution was prepared according to the following formula: FABr, MABr (methyl ammonium bromide), GABr (guanidinium hydrobromide), CsBr and PbBr2 were dissolved in 1 mL of DMSO at a molar ratio of 0.756:0.108:0.216:0.12:1 to prepare a mixed cationic precursor solution (FA 0.7 MA 0.1 GA 0.2 ) 0.9 Cs 0.1 PbBr3, and then add N-vinyl pyrrolidone (NVP) solution equivalent to 20% of the volume of DMSO to the solution (0.2wt% azobisisobutyronitrile equivalent to the mass of N-vinyl pyrrolidone is added to NVP in advance) to obtain a perovskite precursor solution.

[0074] S2 and S3 are the same as in Example 1;

[0075] S4: Dissolve TPBi (1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene) in chlorobenzene (CB) to prepare an antisolvent (concentration of 1.5 mg / mL). Stir the solution at room temperature overnight in a N2 glove box before use. Other steps are the same as in Example 1.

[0076] S5: Finally, the thermal evaporation system is used to -4 Under high vacuum conditions of Pa, a ZADN electron transport layer (ETL) (45nm) and LiF / Al electrodes (1nm / 100nm) were deposited on the perovskite film to obtain a perovskite light-emitting diode.

[0077] This embodiment also provides a perovskite light-emitting diode prepared by the above preparation method.

[0078] Comparative Example 1

[0079] The preparation method of the perovskite light-emitting diode of this comparative example 1 is the same as that of Example 1, except that NVP is omitted in S1.

[0080] In order to verify the performance of the light-emitting diode based on the cubic perovskite thin film, the following experiment was conducted to verify its effect.

[0081] Test Example 1

[0082] In order to explore the morphology of the perovskite films prepared in step S4 of Examples 1 to 5 and Comparative Example 1, the surface SEM of the corresponding films was tested. The results are as follows: Figure 3 shown.

[0083] Depend on Figure 3It can be seen that the perovskite of the film of comparative example 1 presents a crystal morphology of different sizes, roundness, and more holes, and the grain size is mostly about 200nm, and the arrangement is disorderly. After adding the self-polymerization additive NVP, the morphology of the perovskite film in Examples 1-5 changes greatly, from the original rounded bulk grains to uniform, cubic crystals, and the grain size is reduced to 100nm; especially with the increase of NVP content, the cubic phase is more obvious, and after reaching a certain amount (15vol.%), the SEM image is blurred. The reason is that the polyvinyl pyrrolidone (PVP) formed after the polymerization of NVP has poor conductivity. At this time, there is a large amount of polymer PVP in the perovskite film. The electron beam hits the perovskite film, and the reflected electrons are very few, resulting in the SEM image taken being very dark.

[0084] In order to further observe the changes in film morphology, taking Example 1 and Comparative Example 1 as examples, the cross-sectional SEM images of the corresponding films were tested. Figure 4 shown.

[0085] Depend on Figure 4 The thickness and grain boundary of the perovskite film can be seen. It is found that the grain size of the perovskite film in Comparative Example 1 is larger than that in Example 1, and its film thickness is about 280nm. The thickness of the perovskite film in Example 1 (W / NVP) is about 320nm. The grain boundaries of the perovskite film in Example 1 are significantly reduced, the perovskite grains are more regular and dense, and the black gap in the middle is the NVP after cross-linking.

[0086] Therefore, the present invention can reduce the grain size of thin film perovskite by adding the self-polymerizing additive NVP, effectively increase the charge carrier confinement, and can be used to prepare PeLED devices.

[0087] Test Example 2

[0088] High-resolution transmission electron microscopy (HR-TEM) was used to test the distribution of NVP in perovskite films. Figure 5 shown. Figure 5 (a) is a TEM image of the perovskite film of Comparative Example 1; Figure 5 (c) is a magnified TEM image of the perovskite film of Comparative Example 1; Figure 5 (b) is a TEM image of the perovskite film of Example 1; Figure 5 (d) is a magnified TEM image of the perovskite film of Example 1;

[0089] from Figure 5 (a) Figure 5(b) confirms that NVP is in situ polymerized in the perovskite film and exists at the grain boundary with the perovskite. The edge of the perovskite in the film of comparative example 1 is clear and obvious, while the surface of the perovskite film with NVP added is covered with polymerized PVP. A careful observation shows that the perovskite grains are neatly arranged in a cubic shape, which corresponds to the SEM image. According to the enlarged TEM image (such as Figure 5 (c) Figure 5 As shown in (d), the grain boundary edge of the film of comparative example 1 is clear and there is no amorphous state, while the edge of the perovskite film of example 1 (after adding NVP) has an amorphous amorphous morphology, which indicates that the polymer PVP exists at the edge of the perovskite grains or between the grains. The selected area electron diffraction (SAD) results show that the perovskite film with NVP added has dense crystals, clear lattices, and the lattice spacing (d) is respectively and They correspond to the (100) and (200) crystal planes of the three-dimensional perovskite, respectively. Only the (200) crystal plane exists in the perovskite film of Comparative Example 1. The reason for obtaining high-quality cubic phase grains is that during the crystallization of perovskite, the impurity phase is repelled to the edge and wrapped by PVP. The experimental results of SEM and TEM have preliminarily confirmed that NVP undergoes self-polymerization during the annealing process of perovskite, and the polymer exists in the perovskite grain boundary.

[0090] Test Example 3

[0091] The green perovskite light-emitting diodes prepared in Examples 1 to 5 and Comparative Example 1 were placed in a glove box to characterize the electrical properties of the devices. The characterization results are shown in FIG. Figure 6 and Figure 7 shown. Figure 6 (a) to Figure 6 (c) The current density-voltage characteristic curve, brightness-voltage characteristic curve, EQE-current density characteristic curve of the PeLEDs devices of Examples 1 to 5 and Comparative Example 1, respectively. Figure 6 (d) is the EL spectrum of the PeLED prepared in Example 1 at different voltages.

[0092] Figure 6 (a) shows the current density-voltage curve. Under voltage drive, the current density of PeLEDs devices with different volume ratios of NVP doping content is different. Specifically, with the increase of NVP content, the current density first increases and then decreases. The smaller the current density before lighting, the better, which can represent the size of the leakage current. The larger the current density after lighting, the better, indicating the balance of carrier recombination. Figure 6 (b) and Figure 6 (c) It can be seen that when the NVP doping volume ratio is 5 vol.%, the current density is the highest and the corresponding luminescence brightness is also the highest, reaching 240000 cd m -2The optimized devices achieved EQE of 4.21% (W / 2.5 vol.%), 9.32% (W / 5 vol.%), 7.43% (W / 10 vol.%), 6.32% (W / 15 vol.%), and 5.36% (W / 20 vol.%), which were all higher than the device in comparative example 1 (3.54%).

[0093] Figure 6 (d) shows the normalized EL spectrum of PeLED under different voltages. When driven from 3V to 7V, PeLED exhibits stable green light emission at 540nm, which is consistent with the PL spectrum. The emission peak intensity of PeLED increases with the increase of voltage, and the peak position does not move with the increase of external bias voltage, indicating that the spectrum of PeLED device is stable after adding NVP.

[0094] Figure 7 The trap state density diagram of the perovskite thin film of Example 1 and Comparative Example 1, where Figure 7 (a) is the trap state density diagram of the perovskite thin film in comparative example 1, Figure 7 (b) is the trap state density diagram of the perovskite film in Example 1. Figure 7 It can be seen that compared with the device of comparative example 1, the hole defect state density (N t ) is relatively low, and the hole defect state densities of the devices of Comparative Example 1 and Example 1 are 2.99×10 16 cm -3 , 1.07×10 16 cm -3 , trap filling threshold voltage (V TFL ) is 0.57V and 0.45V, V TFL The decrease in the value indicates that the density of trap states in the film decreases.

[0095] Test Example 4

[0096] The presence of ion migration in perovskite will cause the diffusion of vacancy defects and accelerate the degradation of effective carrier recombination. The degradation of PeLED during operation is mainly related to the quality of the perovskite film. The self-polymerization additive NVP can improve the photostability of the perovskite film. The perovskite films of Example 1 and Comparative Example 1 were continuously tested by PL within 30 days.

[0097] like Figure 8 (a) and Figure 8 As shown in (b), the PL intensity of the perovskite film of Comparative Example 1 is reduced to 50% of the original after 20 days, while the perovskite film of Example 1 after adding NVP does not change much within 30 days, which allows the film to maintain a high fluorescence emission for a long time.

[0098] Test Example 5

[0099] In order to further verify whether the PL and EL spectra are consistent, the EL test was performed on the devices prepared in Example 1 and Comparative Example 1 at a voltage of 4.6 V. Fig. 9 (a) and Fig. 9 As shown in (b), the EL spectrum of the perovskite film in comparative example 1 is different from the PL spectrum. The emission peaks of PL and EL are centered at 540nm and 537nm, respectively. The blue shift in the EL spectrum is likely caused by free carrier emission. The PL of the perovskite film of Example 1 (W / NVP) matches well with the EL of the device. The EL is broadened compared to the PL, which can be attributed to the Stark effect induced by the electric field. In general, the spectral performance of the perovskite film with the introduction of NVP additives is more stable.

[0100] Test Example 6

[0101] The PeLEDs prepared in Example 1 and Comparative Example 1 were subjected to a constant voltage of 3.4 V (in a glove box filled with N2, with an initial brightness of 3000 cd m -2 ) was tested for operational stability, and the results are as follows Fig.10 shown.

[0102] from Fig.10 It can be seen that the half-life (T50) of the target device is 90 min, which is more than six times longer than the 15 min of the original device, indicating that NVP can enhance the stability of the device during operation.

[0103] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. All other embodiments obtained without creative work and related deductions and substitutions made by ordinary technicians in the field under the conditions of the concept of the present invention belong to the scope of protection of the present invention.

Claims

1. A method for preparing a light-emitting diode based on a cubic perovskite thin film, characterized in that: The following steps are involved: S1. Prepare a precursor solution: dissolve FABr, MABr, GABr, CsBr and PbBr2 in DMSO to obtain a mixed cationic precursor solution, and then add N-vinyl pyrrolidone and azobisisobutyronitrile to obtain a precursor solution; S2, cleaning and drying the conductive substrate; S3, coating a mixed solution of PEDOT:PSS and PFI on a conductive substrate, and annealing to obtain a hole transport layer; S4, coating the precursor solution on the hole transport layer, then dropping an anti-solvent, and obtaining a cubic perovskite film after annealing; S5. Depositing an electron transport layer and a cathode on the perovskite film.

2. The method for preparing a light-emitting diode based on a cubic perovskite thin film according to claim 1, characterized in that: The molar ratio of FABr, MABr, GABr, CsBr and PbBr2 in step S1 is (0.74-0.76):(0.1-0.2):(0.2-0.25):(0.1-0.13):

1.

3. According to the method for preparing a light-emitting diode based on a cubic perovskite thin film according to claim 1, the usage ratio of PbBr2 to DMSO in step S1 is 1 mol: (1-2) mL.

4. The method for preparing a light-emitting diode based on a cubic perovskite thin film according to claim 1, characterized in that: The amount of N-vinyl pyrrolidone used in step S1 is 2.5% to 20% of the volume of DMSO.

5. The method for preparing a light-emitting diode based on a cubic perovskite thin film according to claim 1, characterized in that: The amount of azobisisobutyronitrile used in step S1 is 0.1-0.5% of the mass of N-vinyl pyrrolidone.

6. The method for preparing a light-emitting diode based on a cubic perovskite thin film according to claim 1, characterized in that: The anti-solvent in step S4 is a chlorobenzene solution of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, wherein the concentration of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene in chlorobenzene is 0.5-2 mg / mL.

7. The method for preparing a light-emitting diode based on a cubic perovskite thin film according to claim 1, characterized in that: The annealing temperature in step S3 is 140-150° C. and the annealing time is 30-45 min.

8. The method for preparing a light-emitting diode based on a cubic perovskite thin film according to claim 1, characterized in that: The annealing temperature in step S4 is 75-85° C. and the annealing time is 8-15 min.

9. A light-emitting diode based on a cubic perovskite film, characterized in that: The preparation method is described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of polymer / perovskite composite material

    CN111533842A

  • Precursor solution, perovskite thin film, perovskite assembly and preparation method thereof

    CN114551722A

  • Preparation method of high-temperature-resistant basement membrane for IME technology

    CN118290716A